Digital Marketing and Customer Loyalty in the Cosmetic Industry: The Role of Consumer Engagement and Service Quality in the Wardah Brand - Putri Nurmalasari; Mawar Ayu Lestari; Gina Aulia Dewi; Faridz Nugroho; Langgeng Sri Handayani (Score: Jurnal Lentera Manajemen Pemasaran, 2025)
This study is motivated by the decline in customer loyalty toward the Wardah cosmetic brand amidst the increasingly intense competition in the beauty industry. The main objective of this research is to analyze the influence of digital marketing on customer loyalty by considering consumer engagement as a mediating variable and service quality as a moderating variable. This research employs a quantitative approach with descriptive and verification methods, utilizing Structural Equation Modeling–Partial Least Square to examine the relationships between variables. The respondents involved were Wardah product users with experience in digital shopping. The findings indicate that consumer engagement and service quality have a significant direct influence on customer loyalty. Conversely, digital marketing does not have a direct impact on loyalty, but it does have an indirect effect through consumer engagement. Additionally, service quality does not significantly moderate the relationship between the other variables and customer loyalty. The conclusion of this study is that the success of digital marketing in building loyalty depends on how emotionally and actively engaged consumers feel with the brand, as well as how well the service provided meets customer expectations.